2022
DOI: 10.1109/access.2022.3165028
|View full text |Cite
|
Sign up to set email alerts
|

A Multiphysics Modeling of Electromagnetic Signaling Phenomena at kHz-GHz Frequencies in Bacterial Biofilms

Abstract: This paper presents a model that describes a possible mechanism for electromagnetic (EM) signal transmission and reception by bacterial cells within their biofilm communities. Bacterial cells in biofilms are embedded into a complex extracellular matrix containing, among other components, charged helical nanofibrils from amyloid-forming peptides. Based on the current knowledge about the nanoscale structure and dynamics of the amyloids, we explore a hypothetical model that the mechanical vibration of these nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Likewise, there exists a clear link between the mechanical properties of a membrane and its properties, and in turn its functionality, which has motivated research investigating the relationship between membrane vibration and cellular activity. Recently, this line of thinking has been used to show that vibrations can be used as a means of distinguishing among microorganisms [ 22 , 23 ], and to study the interactions between membranes and anchored or adjacent external structures, like in bacterial biofilms [ 24 , 25 ]. Moreover, an increasing number of studies have identified modes of membrane-adjacent structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, there exists a clear link between the mechanical properties of a membrane and its properties, and in turn its functionality, which has motivated research investigating the relationship between membrane vibration and cellular activity. Recently, this line of thinking has been used to show that vibrations can be used as a means of distinguishing among microorganisms [ 22 , 23 ], and to study the interactions between membranes and anchored or adjacent external structures, like in bacterial biofilms [ 24 , 25 ]. Moreover, an increasing number of studies have identified modes of membrane-adjacent structures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increasing number of studies have identified modes of membrane-adjacent structures. For example, functional amyloid fibers, proteinaceous fibers that grow in biofilm and anchor to the bacterial membranes, have been suggested to mechanically vibrate and deliver a damped vibrational signal to an adjacent bacterial cell [ 24 , 25 , 26 ]. Electromagnetic signals on the order of kHz of bacterial DNA that match DNA extracted from Alzheimer’s and other amyloid-induced diseased patients [ 27 ] suggest that bacterial infections are present in such illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…The 2β PSMα1 amyloid nanofiber model can be used to study nanofiber−antimicrobial interactions to elucidate a mechanism for biofilm manipulation using man-made antiamyloid biomimetic nanostructures, as well as to explore the propagation of vibrations across functional amyloids anchored to bacterial membranes. 44,45,50,51 In addition to machine learning techniques recently developed by our team, 46,53 this study provides a structural understanding of amyloid fibers that can inform a set of MD-based design principles and can usher in an era of tailor-made NPs as nanobiotics as high-efficacy antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…We find compelling evidence that a cross-β-sheet two-protofilament (2beta) structure is the most plausible structural model for PSMα1 nanofibers in solution that matches the experimental values of chirality, diameter, and helical periodicity (pitch) of mature PSMα1 nanofibers in solution. The 2β PSMα1 amyloid nanofiber model can be used to study nanofiber–antimicrobial interactions to elucidate a mechanism for biofilm manipulation using man-made antiamyloid biomimetic nanostructures, as well as to explore the propagation of vibrations across functional amyloids anchored to bacterial membranes. ,,, In addition to machine learning techniques recently developed by our team, , this study provides a structural understanding of amyloid fibers that can inform a set of MD-based design principles and can usher in an era of tailor-made NPs as nanobiotics as high-efficacy antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%